Intraoperative central nipple biopsy in nipple‐sparing mastectomy— A retrospective analysis of 211 patients. Issue 4 (23rd February 2021) - Eichler, Christian; Stephan, Sophia; Thangarajah, Fabinshy; Puppe, Julian; Rahmani, Neda; Kurbacher, Christian; Malter, Wolfram; Warm, Mathias
Abstract: Subcutaneous nipple sparing mastectomies (NSM) are an important tool in modern oncoplastic surgery. Especially when an immediate implant‐based reconstruction (IBR) is desired, clean margins are of the utmost importance. Central nipple biopsies during surgery serve two main purposes. Most importantly, it is hypothesized that intraoperative pathological evaluation of this biopsy may increase clean margin resection rates. In addition, a general recurrence risk reduction may occur due to the elimination of glandular and ductal components within the nipple. This analysis is a single center, multi‐surgeon, retrospective, head to head analysis. Starting in March 2015, intraoperative central nipple biopsy in NSMs with IBR was introduced at the Municipal Breast Cancer Centre Cologne, Holweide, Germany. This trial retrospectively evaluates global complication rates, clean margin status and local recurrence rates for cohort 1 (NSM/no nipple biopsy, n = 103) vs. cohort 2 (NSM with nipple biopsy, n = 108) Median follow‐up was 15 months. All implant‐based reconstruction procedures used an epipectoral implant pocket. Cohorts were comparable. Global complication rates slightly favored the nipple biopsy cohort with respects to implant loss rate. An involved central nipple biopsy was found in 4.6% ( n = 5/108) of the performed NSM procedures leading to the immediate removal of the nipple areola complex. All positive retro‐areolar biopsies correlated with a positive nipple biopsy. However, in n = 1 case we found DCIS discontinual proliferation with an involved nipple biopsy, without a correlating positive retro‐areolar biopsy (ie, 1 false‐negative case was prevented). For the 15 month follow‐up, there was no case of local recurrence within nipple areola complex for both cohorts. With this retrospective head to head analysis of 211 patients, it was shown that the central nipple biopsy correlates well with the retro‐areolar biopsy. There may be a reduction in false negative rates. The procedure is safe to use and should be offered to NSM patients.